The Advanced Mesospheric Temperature Mapper: 2-D Measurement of Mesopause Temperatures at King Sejong Station, Antarctica - Ji Eun Kim; Jeong-Han Kim; Geonhwa Jee; Trond S. Trondsen; Craig Unick; Devin Wyatt; Hosik Kam (Journal of Astronomy and Space Sciences, 2025)
The tip of the Antarctic Peninsula is widely recognized as one of the most active regions for gravity wave activity. Situated in this dynamic area, the King Sejong Station (KSS: 62.22°S, 58.78°W) serves as an ideal location for investigating gravity wave activity in the mesosphere and lower thermosphere (MLT) region. The Korea Polar Research Institute (KOPRI) has been operating a meteor radar (MR) and an airglow all-sky camera (ASC) at KSS for over a decade, enabling studies on gravity wave activity and MLT dynamics. To enhance these observational capabilities, a new optical instrument, the Advanced Mesospheric Temperature Mapper (AMTM), was installed in January 2023. The KSS-AMTM provides hydroxyl (OH) airglow intensities at approximately 87 km altitude as well as two-dimensional temperature maps at a high temporal resolution. This study presents a brief overview of the observational features and operation of the instrument, alongside initial results obtained over 28 clear nights from February to October 2023. As part of the initial validation, observed mesopause temperatures were compared with data from meteor radar and the Microwave Limb Sounder onboard the Aura satellite.